Productions : Lothar Baumgarten - Daniel Buren - Marie Bourget - Les Coleman - Tony Cragg - Bill Culbert - Simon Cutts - Louise Davies - Ian Hamilton Finlay - Hamish Fulton - Gilbert & George ; Richard Long ; Ulrich Ruckriem - Richard Tuttle - Lawrence Weiner. (London : Victoria Miro Gallery, 1988)
Baumgarten, Lothar ; Buren, Daniel ; Bourget, Marie ; Coleman, Les ; Cragg, Tony ; Culbert, Bill ; Cutts, Simon ; Davies, Louise ; Hamilton Finlay, Ian ; Fulton, Hamish ; Gilbert & George ; Long, Richard ; Rückriem, Ulrich ; Tuttle, Richard ; Weiner, Lawrence
Productions : Lothar Baumgarten - Daniel Buren - Marie Bourget - Les Coleman - Tony Cragg - Bill Culbert - Simon Cutts - Louise Davies - Ian Hamilton Finlay - Hamish Fulton - Gilbert & George ; Richard Long ; Ulrich Ruckriem - Richard Tuttle - Lawrence Weiner, Victoria Miro Gallery, London, 28 June to 31 July 1988
boek